HGG-07. CYCLIN-DEPENDENT KINASES AS TARGET STRUCTURES FOR CANCER THERAPY – A COMPARATIVE IN VITRO ANALYSIS ON PATIENT-DERIVED GLIOBLASTOMA CELL CULTURE MODELS. (4th December 2020) - Riess, Christin; Classen, Carl Friedrich; Maletzki, Claudia
Abstract: INTRODUCTION: Current therapeutic approaches have limited clinical success for Glioblastoma patients, making novel strategies urgent. Cyclin-dependent kinases (CDK) are crucial in cell cycle, oncogenic transcription, DNA repair, and stem-cell renewal. Glioma cells frequently show genomic alterations in CDKs. Here, we evaluated the antitumoral activity of selective CDK inhibitors (CDKI) abemaciclib (CDK4/6), palbociclib (CDK4/6), and dinaciclib (CDK1/2/5/9) alone and in combination with chemo-/radiotherapy. MATERIALS/ METHODS: Low passage glioblastoma cell lines (N=5) with different molecular characteristics were cultured in 2D and 3D (neurospheroids (NSPs), glioma stem-cells (GSCs). The impact of CDKI alone or in combination with TMZ and radiation (2Gy) was examined. Viability was measured using Calcein-AM and 3D-Glo assays; DNA double-strand breaks by γ-H2AX immunofluorescence. Functional analyses were performed from a 2D culture (72h treatment). RESULTS: Dinaciclib significantly affected viability of GBM cell lines even shortly after low-dose treatment. CDK 4/6 inhibitors were less effective. Abemaciclib and dinaciclib acted radio-sensitizing. Dinaciclib combined with different substances (72h, dose: IC20 ), synergistically potentiated antitumoral effects. In a scratch assay, abemaciclib decelerated wound healing; dinaciclib even induced cell death. Microarray analysis revealed altered gene expression: Genes mediating cell adhesion, division, DNA-binding, apoptosis ( Casp3, Casp8 ), senescence ( ASF1A, CENPA, FBXO31 ), and autophagy ( ATG4D, ATG2A, SOGA1 ) were upregulated. Chemotaxis-mediating (CXCL8, CCL20 ) and proto-oncogenes like JUNB and FOS were strongly down-regulated. Long-term treatment induced dinaciclib resistance in 1/5 cases, and none abemaciclib-treated cells. This was reversed when dinaciclib was combined with TMZ. CONCLUSION: Our results demonstrate strong anti-GBM activity of dinaciclib and abemaciclib, with additive effects of chemotherapy and radiosensitization, encouraging to move forward this strategy.